2010
DOI: 10.2353/ajpath.2010.090690
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity of the Anticancer Therapeutic Agent Bortezomib

Abstract: Recent case reports provided alarming signals that treatment with bortezomib might be associated with cardiac events. In all reported cases, patients experiencing cardiac problems were previously or concomitantly treated with other chemotherapeutics including cardiotoxic anthracyclines. Therefore, it is difficult to distinguish which components of the therapeutic regimens contribute to cardiotoxicity. Here, we addressed the influence of bortezomib on cardiac function in rats that were not treated with other dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
93
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(98 citation statements)
references
References 36 publications
3
93
0
2
Order By: Relevance
“…Bortezomib, by inhibiting ubiquitin-proteasome pathway, would lead to accumulation of ubiquitinated proteins in cardiac myocytes 5 . None of necrotic or apoptotic cells are found in histopathological heart examination and no rise in troponin I levels 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Bortezomib, by inhibiting ubiquitin-proteasome pathway, would lead to accumulation of ubiquitinated proteins in cardiac myocytes 5 . None of necrotic or apoptotic cells are found in histopathological heart examination and no rise in troponin I levels 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Recomenda-se manter o paciente em normovolemia e utilizar com cautela anti-hipertensivos durante o tratamento com o bortezomibe. Estudo experimental recente demonstra que o bortezomibe pode resultar em disfunção ventricular esquerda, por reduzir a síntese do ATP e reduzir a contratilidade dos cardiomiócitos 236 . Esses dados apontam para a necessidade de monitorização adequada dos pacientes em uso de bortezomibe para a detecção de possível cardiotoxicidade 236 .…”
Section: Mitomicina: a Mitomicina C é Um Agente Derivado Dounclassified
“…Nowis et al [74] reported that bortezomib treatment leads to left ventricular contractile dysfunction in rats manifested by a significant drop in left ventricle ejection fraction. It is important that in this study rats were not treated with other drugs.…”
Section: Mechanism Of Cardiotoxicity Of Bortezomibmentioning
confidence: 99%
“…Dramatic ultrastructular abnormalities of cardiomyocytes, especially within mitochondria, were accompanied by decreased ATP synthesis and decreased cardiomyocyte contractility. [74] Bortezomib induced cardiac effects seem to be reversible. The risk of cardiotoxicity after bortezomib is higher in patients which have previously cardiac problems or being concomitantly treated with other chemotherapeutics including cardiotoxic anthracyclines.…”
Section: Mechanism Of Cardiotoxicity Of Bortezomibmentioning
confidence: 99%